2017
DOI: 10.1097/coh.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated immune exclusion of HIV

Abstract: Purpose of review Although approximately 90% of all HIV transmissions in humans occur through mucosal contact, the induction of mucosal anti-HIV immune responses has remained understudied. Here we summarize data demonstrating the powerful protection that is achievable at mucosal frontlines through virus-specific mucosal IgA alone or combined with IgG. Recent findings Passive immunization with different monoclonal antibody (mAb) subclasses but identical epitope specificity (the conserved V3-loop crown of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Passive immunization with mucosally administered, monoclonal dIgAs is depicted in Figure 2 A. Any significant prevention of SHIV acquisition would have to occur in the mucosal lumen by trapping infectious virion in large complexes to prevent mucosal transcytosis; this process is called immune exclusion ( 10 , 31 ). This information needs to be generated in order to assess the role of mucosal B cells and anti-HIV mucosal antibodies in preventing virus acquisition—key data for future vaccine design against a pathogen that is predominantly transmitted via mucosal routes.…”
Section: Harnessing Mucosal Iga To Protect the Hostmentioning
confidence: 99%
“…Passive immunization with mucosally administered, monoclonal dIgAs is depicted in Figure 2 A. Any significant prevention of SHIV acquisition would have to occur in the mucosal lumen by trapping infectious virion in large complexes to prevent mucosal transcytosis; this process is called immune exclusion ( 10 , 31 ). This information needs to be generated in order to assess the role of mucosal B cells and anti-HIV mucosal antibodies in preventing virus acquisition—key data for future vaccine design against a pathogen that is predominantly transmitted via mucosal routes.…”
Section: Harnessing Mucosal Iga To Protect the Hostmentioning
confidence: 99%
“…In this study we examined mucosal antibodies induced by two different modalities of candidate HIV/SIV vaccines, a vaccine targeting short peptide sequences overlapping the 12 protease cleavage sites and a vaccine targeting full Gag and Env of SIVmac239. Since 90% of HIV transmissions occur through the mucosal route [ 68 ] and male to female sexual transmissions account for more than half of all HIV infections [ 53 ], it is important to test whether a candidate vaccine can induce mucosal immune responses to HIV/SIV antigens. Our study showed that both the PCS vaccine and Gag/Env vaccine can induce cervicovaginal mucosal IgG antibodies to SIV antigens, including PCSs, Gag and Env.…”
Section: Discussionmentioning
confidence: 99%
“…There are also other gp41 epitopes that have induced antibodies with the ability to block HIV-1 transcytosis [47][48][49] and support the antibody-dependent cellular cytotoxicity activity 50,51 . Antibodies can also promote immunoglobulin-mediated mucus entrapment of virions 52,53 or other Fc-mediated antibody effector functions 54 , and synergies among IgG and IgA toward gp41 and/ or gp120 can offer better virus inhibition and protection 50,55 . The reported conserved epitopes on gp41 make this viral protein another very attractive antigen that could be included in prophylactic HIV-1 vaccines for establishing front-line defenses at the primary mucosal entry point used by HIV-1 to prevent virus transmission, local infection, and dissemination.…”
Section: Introductionmentioning
confidence: 99%